Economic costs and benefits of promoting healthy takeaway meals at workplace canteens - Jørgen Dejgaard Jensen; Morten Raun Mørkbak; Jonas Nordström (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2011)
Canteen Takeaway is a novel concept, which entails workplace canteens to utilise existing production capacity to supply packaged meals for employees to bring home. The concept has a potential to raise the average nutritional quality of employees' diets. The purpose of the study is to assess the economic net gains for users, and for society as a whole, of promoting healthy canteen takeaway meals, using Danish workplaces as an example. The analytical framework for the study combines direct cost analyses, users' willingness to pay estimated through a choice experiment and cost-of-illness methods to assess the net society costs and benefits associated with an extended use of canteen takeaway meals as a health promotion strategy. The results show that employees have a positive willingness to pay for health attributes in canteen takeaway meals, but with a minority having a highly negative willingness to pay for the canteen takeaway concept. The potential health effects of a healthy canteen takeaway programme are estimated to be positive, but modest in magnitude. The estimated costs of providing healthy canteen takeaway meals exceed the sum of average direct and indirect benefits. In conclusion, healthy CTA programmes seems to be an economically sustainable intervention at some workplaces, though the analysis does not fully support a full-scale implementation of healthy CTA programmes at Danish workplaces from a welfare economic perspective.
Keywords: D12; D61; I18; 330; Cost-benefit analysis; Daly; Choice Experiment; Canteen take-away meals; Health